2012
DOI: 10.1620/tjem.227.217
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Ameliorates Muscle Cramps of Hemodialysis Patients: A Prospective Trial

Abstract: Patients with renal failure undergoing hemodialysis often have muscle cramps during and after the dialysis therapy. Muscle cramps are defined as the sudden onset of a prolonged involuntary muscle contraction accompanied with severe pain, resulting in early termination of a HD session and inadequate dialysis. The etiology of the cramps is unknown and effective anti-cramp medicine is not available. We have hypothesized that water-soluble vitamins are deficient in HD patients. Accordingly, we administrated biotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
1
28
1
Order By: Relevance
“…It was developed by the researcher after review of relevant literature (19,(20)(21)(22) and it consisted of two parts: Part (I): it included the following items related to leg cramps: 1. Site (right leg, left leg or both legs) 2.…”
Section: Tool Iii: Leg Cramps Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It was developed by the researcher after review of relevant literature (19,(20)(21)(22) and it consisted of two parts: Part (I): it included the following items related to leg cramps: 1. Site (right leg, left leg or both legs) 2.…”
Section: Tool Iii: Leg Cramps Assessmentmentioning
confidence: 99%
“…Leg cramps are defined as the sudden onset, painful and prolonged involuntary muscle contraction that may be visible or palpable (1,2) . Despite the "benign" nature of cramps, many patients find the symptom very uncomfortable (3).…”
Section: Introductionmentioning
confidence: 99%
“…Scores were measured before and after oral biotin administration as reported previously (Oguma et al 2012). Twentyeight HD patients (12 patients without cramps and 16 patients with cramps) and 11 healthy volunteers were studied.…”
Section: Patientsmentioning
confidence: 99%
“…In our previous study (Oguma et al 2012), oral biotin was administered to patients with frequent muscle cramps during HD sessions. The administered biotin promptly reduced the incidence and severity of cramps in most patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Oguma et al, 27 Japanese HD patients found that biotin levels were significantly higher than controls, but the assay used may have been measuring biotin and its metabolites 40 .…”
Section: Evidence For Altered Requirements In Hemodialysis Patientsmentioning
confidence: 99%